Aerobic and anaerobic threshold determined by specific test in judo is not correlated with general test - Azevedo, P.; Carlos Oliveira, J.; Zagatto, A.; Eduardo Pereira, E.; Andrade Perez, S. E. (Sport Sciences for Health, 2018)
The purposes of this study were to compare and correlate the aerobic threshold (THaer), and anaerobic threshold (THanaer) measured during a new single judo-specific incremental test and treadmill test for aerobic demand evaluation. Eight well-trained male competitive judo players (24.3±7.9 years; height of 169.3±6.7 cm; the fat mass of 12.7±3.9%) performed a maximal incremental specific test for judo mimicking the Uchi-komi drills and on the treadmill in different days. There was a difference between specific and general THaer (P=0.0006) as well as a weak correlation for THaer (r=0.32; R2=0.1; P=0.2) and THanaer (r= -0.31; R2=0.1; P=0.12). When correlation was applied to normalized data (percentage of peak load), we observed moderate correlation for THaer (r=0.76; R2=0.58; P=0.027), but the same result was not observed for THanaer. We conclude that there is a need for THaer and THanaer evaluation through a specific test for Judo.